Effect of feeding different level of Moringa oleifera leaf meal on growth performance, lipid profile and meat fatty acid composition of Vanaraja chicken in tropics - KUMAR, ABHISHEK; KUMAR, KAUSHALENDRA; KUMAR, SANJAY; CHANDRAMONI; SINHA, R R K; PASWAN, J K; MANDAL, G P (The Indian Journal of Animal Sciences, 2017)
Present study was designed to investigate the dietary inclusion of Moringa oleifera leaf meal (MOLM) on growth performance, lipid profile and meat fatty acid composition of Vanaraja birds under tropical condition. The experiment was conducted for 56 days on 300 Vanaraja birds divided into 5 different treatment groups of 60 birds each. T1 served as control group and fed only with basal ration whereas, other treatment groups such as T2, T3, T4 and T5 were supplemented with 5, 10, 15 and 20% Moringa oleifera leaf meal along with basal ration. Growth performance and feed conversion efficiency in Vanaraja chicken showed significant effect and good fluctuation was observed among the different treatment groups. The total cholesterol and triglyceride level decreased significantly as compared to control group. The fatty acid composition in chicken was significantly improved. However, the maximum profit per kg live weight was noted in T2 group and least profit observed in 20% MOLM fed group. It was concluded that the overall performances improved significantly with 5% followed by 10% Moringa oleifera leaf meal supplemented birds with achieving maximum profit and healthy meat production for human consumption.